Interactions of amino acid enantiomers with chiral target in high and low energy collisions. (July 2015) - Rebrov, O; Kulyk, K; Ryding, M; Stocket, M; Alexander, J; Zettergren, H; Schmidt, H; Cederquist, H; Thomas, R D; Uggerud, E; Larsson, M
Synopsis: The study is focused on investigation of stereospecific interaction of amino acid enantiomers with chiral targets in collisions of 1 keV and ∼ 1 eV energy using tandem mass spectrometry.